The future of Asian FTAs and trade blocs after Covid-19 - Bendebka, Ramzi (Asia Power Watch, 2020)
With the Covid-19 pandemic, the Asia-Pacific region (APAC) is facing a new challenge to its economic and trade engine. As the virus kept spreading, global economic issues and public health took center stage in Asia-Pacific countries from the beginning of 2020 until today. As a result, the IMF growth forecast for the region stands at zero percent in 2020, the worst performance in 60 years, with China’s growth declining from 6.1% in 2019 to a projected 1.2% in 2020. An even more significant contraction is expected in the US, where GDP growth could drop to -6% in 2020. This grim outlook raises the question of the future of regional cooperation and trade agreements in Asia-Pacific, and how countries will adapt in the post-COVID-19 world.